Language contact and translation in religious context ... : Comparative approaches ... - Calenda (OpenEdition, 2018)
This conference brings together anthropologists and linguists working on conversion, cultural transmission and translation theory, as well as on various case studies, whose geography comprises Oceania, Amazonia, Yucatan, Sub-Saharan Africa, Middle East, Europe, Alaska and Chukotka (Russia), and whose temporal frame spreads from the Hellenistic era to the Spanish colonization of the Americas and to the present time. The main questions of the conference are the modalities of the ethnolinguistic encounter and translation accompanying religious conversion, whether, and how, the language gets altered as a result of these processes, and what are the broader cognitive and sociocultural consequences that accompany the linguistic transformation. ...